1981
DOI: 10.1017/s0305000900003445
|View full text |Cite
|
Sign up to set email alerts
|

Semantic roles and residual grammatical categories in mother and child speech: who tunes into whom?

Abstract: Mother and child speech in two half-hour free play conversations of six pairs were analysed for 15 semantic roles such as AGENT and ACTION, and five additional syntactic categories such as negation. Children were taped at the beginning of word combinations (1; 7–2; 0) and again 3 to 6 months later. Mothers and children were similar to one another in the relative frequency with which they used the different semantic and syntactic categories. However, the mothers' use was stable, including a larger number of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 3 publications
3
16
0
1
Order By: Relevance
“…This argument is consistent with recent data suggesting that the fine-tuning hypothesis is poorly supported (Retherford et al, 1981). This argument is consistent with recent data suggesting that the fine-tuning hypothesis is poorly supported (Retherford et al, 1981).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This argument is consistent with recent data suggesting that the fine-tuning hypothesis is poorly supported (Retherford et al, 1981). This argument is consistent with recent data suggesting that the fine-tuning hypothesis is poorly supported (Retherford et al, 1981).…”
Section: Discussionsupporting
confidence: 92%
“…This argument is consistent with recent data suggesting that the fine-tuning hypothesis is poorly supported (Retherford et al, 1981). Retherford et al (1981) reported that, by 2 years, mother and child were already well tuned-in to each other. syntactic complexity; MLU; number of semantic categories) on maternal speech.…”
Section: Discussionsupporting
confidence: 92%
“…The definitions for 15 semantic roles and five syntactic categories described by Retherford and colleagues (Retherford, Schwartz, & Chapman, 1981) were utilized; these included categories such as agent, action, object, and entity. Affirmations (i.e., concurrence expressed via any mode of communication) and social conventions (e.g, hi, 'bye' [wave]) were also coded.…”
Section: Codingmentioning
confidence: 99%
“…Retherford et al . (1981) found that the semantic relations expressed in mother's play with their 2‐ and 3‐year‐old children included the full range of relationships that the children were learning to express, and included about 15% of instances of complex syntax well above their children's levels of production.…”
Section: Introductionmentioning
confidence: 99%